PENYULUHAN PENGELOLAAN TANAMAN TERPADU JAGUNG DI KECAMATAN MALLAWA MAROS - -, Haerul - (LPPM Univ. Ibn Khaldun Bogor, 2022)
Mallawa Subdistrict is one of the centers for hybrid maize cultivation in Maros Regency with an average productivity of 4-5 tons/ha with a planting area in 2019 reaching 2000 ha/year and continues to grow every year. The productivity is still far below the genetic potential of the superior varieties planted. The thing that causes the low productivity of maize obtained is because the cultivation management is not optimal. Counseling on integrated maize crop management aims to improve the knowledge, skills and attitudes of farmers in improving integrated maize cultivation techniques. The extension method used is lecture interspersed with discussion. After attending the counseling, farmers can compare the techniques that have been carried out so far with the technology component of integrated maize crop management and plan to adopt things that can be done according to the standard of integrated maize crop management.